2013
DOI: 10.12659/aot.889157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the immunogenetic KIR and HLA systems on long-term renal transplant outcome

Abstract: The present study demonstrates an important role of the KIR immunogenetic system in the long-term immune response to kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In a murine kidney transplant model based on hybrid resistance, NK cells were shown to mediate long-term allograft injury in the absence of T and B cells [ 28 ]. In this context of missing-self recognition, an influence of certain KIR genes was proposed as KIR2DS3 without cognate HLA ligand was associated with better, with ligand with worse effects on kidney function [ 13 ]. In order to improve our understanding of the NK cell repertoire, function and the influence of immunosuppression in our patient cohort after KTx, we investigated receptor expression and response to in vitro stimulation of NK cells derived from KTx recipients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a murine kidney transplant model based on hybrid resistance, NK cells were shown to mediate long-term allograft injury in the absence of T and B cells [ 28 ]. In this context of missing-self recognition, an influence of certain KIR genes was proposed as KIR2DS3 without cognate HLA ligand was associated with better, with ligand with worse effects on kidney function [ 13 ]. In order to improve our understanding of the NK cell repertoire, function and the influence of immunosuppression in our patient cohort after KTx, we investigated receptor expression and response to in vitro stimulation of NK cells derived from KTx recipients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these NK cell subsets in kidney transplantation (KTx) has not been clarified yet, although recent studies revealed that a KIR-ligand mismatch between donor HLA class I molecules and recipient KIR repertoire has no impact on allograft outcome [ 12 ]. In a recent study, however, the presence of the KIR2DS3 gene in KTx recipients was associated with better graft function in the absence of the HLA class I ligand in the donor [ 13 ]. In addition, lower NK cell numbers with increased proportions of CD56 bright NK cells were identified in DSA-positive kidney transplanted patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts [ 22 25 ] have tried to overcome the problems by matching with high accuracy those domains that directly interact with the antigen (exons 2 and 3 for HLA class I, and exon 2 for HLA class II), but this approach has proven to be insufficient alone [ 26 ]. Furthermore, while HLA typing and HLA gene validation are done routinely through molecular genotyping methods [ 27 29 ], the large and rapidly growing number of described HLA alleles are rendering them obsolete and unable to meet current clinical and research throughput demands [ 14 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…KIR genotypes also affect transplantation outcomes. Donor/recipient KIR ligand mismatches reduce graft survival in hepatic and renal transplantation (Kuśnierczyk 2013; La Manna et al 2013; Legaz et al 2013; Van Bergen et al 2011). For instance, Cirocco et al (2007) and Kunert et al (2007) independently found that acute rejection was significantly decreased in transplants involving KIR2DL2+ recipients matched with HLA-C1+ donors compared to HLA-C1 - donors.…”
Section: Introductionmentioning
confidence: 99%